Organoleptic Quality of Cereal Based on Sago Flour with a Combination of Red Spinach Flour for Patients with Diabetes Mellitus - Mustamir Kamaruddin; Sriyanti Sriyanti; Siska Hafid (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the organoleptic quality of cereals based on sago flour with a combination of red spinach flour for diabetics. This type of research is an experiment using a completely randomized design (CRD) with 3 treatments and 6 repetitions. Observations were made by means of organoleptic quality tests. The panelists used were somewhat trained panelists of 30 people. Data were analyzed using the Kruskal Wallis test. The results showed that the red color was close to brownish red (2.3–3.67). Sago flavor (2.47–2.73) and spinach flavor (2.26–2.53). Not sweet (1.07–1.37), sago flavor (2.17–2.4), and spinach flavor (1.93–2.1). Crispy in texture close to very crunchy (2.93–3). Has a difference in color and does not have a difference in aroma, taste and texture. The conclusion is that the red color is close to brownish red. Scented sago and scented spinach. Not sweet, sago and spinach taste. Crispy in texture close to very crunchy, and the color parameters have differences